RIGHT OF FREE MANIFESTATION AND THE CRIMINALIZATION OF SOCIAL MOVEMENTS: THE BODIES IN THE STREET (Fiep Bulletin - online, 2019)
This article aims to demonstrate the relationship between freedom of expression, especially freedom of expression ofsocial movements and their importance to the Democratic State of Law and discuss the consequences of criminalization of thesemovements, when bodies go to the streets. Disagreeing with some naturalistic jus authors, affiliated with the theory of NaturalLaw, which would understand its emergence in a natural, spontaneous way, being superior and prior to human existence, perfectand permanent, of divine origin, suffice the human reason for its knowledge, , law would already be born with man, and, whennecessary for the solution of social conflicts, he would emanate from reason to men. Law, in fact, arises from the daily struggle,from social conflicts, the essence of which is the human and historical construction of law, where human experience, time, cultureand legal fact are the main source from which the law will derive. The law is the imperfect and eternally unfinished human workand in this way it is urgent the struggle for the construction, remodeling and updating of the rights, the political participation, thesocial movements are of extreme value, making that when we put the bodies in the street , let us turn to the insertion of the citizenpower in front of the social demands.